A Pragmatic Study on Conversational Implicatures in the Felicia N. S.’s Humor Politik Indonesia - Santi Wahyufi Diningsih; Andayani; Muhammad Rohmadi (Jurnal Linguistik Terapan, 2020)
Pragmatics is a branch of linguistics whose focus is on meaning expressed by speakers or writers and interpreted by listeners or readers. The benefit of learning a language through pragmatics is that one can speak words about the meaning intended by others. This will be very interesting if the analysis material used is a humor book. The reason for the author to choose humor books as the material to study was to enrich research related to humor discourse. This paper describes the results of a pragmatic analysis of the implied meaning (implicature) as found in the book Humor Politik Indonesia. This study adopted a descriptive qualitative method. The result indicates that the implicatures in the book are expressing satire, expressing request, expressing annoyance, expressing suggestion, expressing reports, rejecting, misleading, mocking, concluding, and criticizing.